Cyclotrons: Why/how are their dynamics different?. (13th March 2023) - Baartman, R.
Abstract: For this issue, papers on the topic of cyclotron beam physics have been solicited and chosen to highlight the main areas both of historic interest and of active research. I take the opportunity to outline the differences and similarities between cyclotron dynamics as compared to other accelerator types. As well, I try to introduce the major areas of interest, referring to papers in this issue, as appropriate.